Development of Polymer and Surfactant Based Naringenin Nanosuspension for Improvement of Stability, Antioxidant, and Antitumour Activity - Shadab Md; Nabil A. Alhakamy; Sohail Akhter; Zuhier A. Y. Awan; Hibah M. Aldawsari; Waleed S. Alharbi; Anzarul Haque; Hira Choudhury; Ponnurengam Malliappan Sivakumar (Journal of Chemistry)
Nanosuspensions are widely reported to enhance the solubility of poorly soluble drugs. In addition to enhancement in solubility, improvement of stability and therapeutic efficacy would be an added advantage. In the present study, premilling and subsequent high-pressure homogenization were carried out to produce naringenin nanosuspension. Hydroxypropyl methylcellulose and sodium dodecyl sulfate were evaluated for their performance as stabilizers under various homogenization cycles. The prepared nanosuspensions were studied for average particle size and size distribution, zeta potential, solubility, drug release, antioxidant activity, and in vitro antitumor activity. It was observed that both hydroxypropyl methylcellulose-stabilized nanosuspension and sodium dodecyl sulfate-stabilized nanosuspension produced an enhancement in physical stability, antioxidant potential, and in vitro cytotoxicity compared with naringenin. Furthermore, hydroxypropyl methylcellulose-stabilized nanosuspension was found to be better than sodium dodecyl sulfate-stabilized nanosuspension in terms of particle size and size distribution, storage stability, and drug release. This study showed that nanosuspension formulations could be a potential strategy for improving dissolution and antitumor activity of naringenin.